Factor VIII organisation on nanodiscs with different lipid composition - Grushin, Kirill; Miller, Jaimy; Dalm, Daniela; Stoilova-McPhie, Svetla (Thrombosis and Haemostasis, 2015)
Nanodiscs (ND) are lipid bilayer membrane patches held by amphiphilic scaffolding proteins (MSP) of ~10 nm in diameter. Nanodiscs have been developed as lipid nanoplatforms for structural and functional studies of membrane and membrane associated proteins. Their size and monodispersity have rendered them unique for electron microscopy (EM) and single particle analysis studies of proteins and complexes either spanning or associated to the ND membrane. Binding of blood coagulation factors and complexes, such as the Factor VIII (FVIII) and the Factor VIIIa - Factor IXa (intrinsic tenase) complex to the negatively charged activated platelet membrane is required for normal haemostasis. In this study we present our work on optimising ND, specifically designed to bind FVIII at close to physiological conditions. The binding of FVIII to the negatively charged ND rich in phosphatidylserine (PS) was followed by electron microscopy at three different PS compositions and two different membrane scaffolding protein (MSP1D1) to lipid ratios. Our results show that the ND with highest PS content (80 %) and lowest MSP1D1 to lipid ratio (1:47) are the most suitable for structure determination of the membrane-bound FVIII by single particle EM. Our preliminary FVIII 3D reconstruction as bound to PS containing ND demonstrates the suitability of the optimised ND for structural studies by EM. Further assembly of the activated FVIII form (FVIIIa) and the whole FVIIIa-FIXa complex on ND, followed by EM and single particle reconstruction will help to identify the protein-protein and protein-membrane interfaces critical for the intrinsic tenase complex assembly and function.
Keywords: Coagulation factors; imaging; phospholipids; electron microscopy; protein structure / folding